The crystal structure of 4-(2-bromoethoxy)-2-hydroxybenzaldehyde, C9H9BrO3 - Gao Dongmei; Zuo Zhenyu (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C9H9BrO3, monoclinic, P21 n (no. 14), a = 10.8914(4) Å, b = 4.6335(2) Å, c = 18.4554(8) Å, β = 97.278(2)°, V = 923.85(7) Å3, Z = 4, T = 225 K, R gt(F) = 0.0385, wR ref(F 2) = 0.0902.